Structural equation modeling of symptom clusters and health-related quality of life among patients with advanced colorectal cancer receiving chemotherapy in Bangkok, Thailand - Suratako, Savitree; Matchim, Yaowarat; Griffin, Mary Quinn (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Patients with advanced colorectal cancer (CRC) receiving chemotherapy experience multiple symptoms due to both disease progression and complications of treatment. These symptoms affect the physical, psychological, and social aspects of health-related quality of life (HRQoL). Additionally, contextual variables of patients may also impact HRQoL. Objective: To test a structural equation model on symptom clusters, contextual variables, and HRQoL in patients with advanced CRC receiving chemotherapy. Methods: In this cross-sectional study, data were collected from 300 patients with advanced CRC who had received chemotherapy at five hospitals in Bangkok, Thailand, between March 2023 and July 2023. Data collection instruments included a demographic data form, Memorial Symptom Assessment Scale, Multidimensional Scale of Perceived Social Support questionnaire, Palliative Care Outcome Scale, and Functional Assessment of Cancer Therapy-Colorectal questionnaire. Structural equation modeling (SEM) was used to test the model. Results: SEM showed a good model fit, with X2/df = 1.15, p = 0.20, CFI = 0.94, TLI = 0.94, RMSEA = 0.03, and SRMR = 0.02. The symptom severity cluster dimension, symptom distress cluster dimension, social support, and palliative care outcomes predicted effects on HRQoL with 78% accuracy. The findings showed that the symptom severity and symptom distress cluster dimensions showed significant negative direct and positive indirect effects on HRQoL. Palliative care outcomes had a significant negative influence on HRQoL. Moreover, social support had direct positive and indirect negative influences on HRQoL. Conclusions: Symptom clusters, social support, and palliative care outcomes were identified as predictors of HRQoL in patients with advanced CRC receiving chemotherapy. Understanding the SEM of symptom clusters, social support, palliative care outcomes, and HRQoL may help nurses and other healthcare professionals develop effective interventions to better manage symptoms in patients with advanced CRC receiving chemotherapy.